Kirguizistán, 2007: oportunidades y desafíos - Alonso, Antonio (UNISCI Discussion Papers, 2007)
In 2005, President Akayev fell as a result of a popular revolution, something that seemed impossible among the regimes of Central Asia. The year 2006 was marked by the new President Bakiev’s attempt to stabilize the situation of the country and to start up the constitutional reform. The year 2007 began, nevertheless, with a return to the authoritarianism of the previous stage, although maintaining the democratic appearance. In the article, the main issues that require a more urgent reform for the quick stabilization of Kyrgyzstan are presented: institutional, economic, territorial, the Islamism and the foreign influences.